Selection of Bacteriocinogenic Bacillus spp. from Traditional Fermented Korean Food Products with Additional Beneficial Properties - Gee Hyeun Choi; Joanna Ivy Irorita Fugaban; Clarizza May Dioso; Jorge Enrique Vazquez Bucheli; Wilhelm Heinrich Holzapfel; Svetoslav Dimitrov Todorov (Fermentation, 2021)
Two Bacillus spp. isolated from kimchi, Bacillus tequilensis ST816CD and Bacillus subtilis ST830CD, were characterized for their antimicrobial properties and safety. The proteinaceous nature of their inhibitory metabolites was confirmed after exposure to proteolytic enzymes, resulting in partial loss of the antimicrobial effect. This indicated that different non-proteinaceous antimicrobial substances may also be produced by these strains. This hypothesis was later confirmed when genes associated with the production of surfactants were detected in their DNA. The expressed antimicrobial metabolites were not affected by treatment at different temperatures and pH levels, including exposure to selected chemicals. Their strong adherence to susceptible pathogens was not significantly affected by different temperatures, chemicals, or pH values. Both Bacillus strains showed inhibitory activity against clinical and food-associated pathogens, including Listeria monocytogenes ATCC 15313, and some Staphylococcus species. Several genes associated with the production of antimicrobial metabolites were detected, but key virulence and beneficial genes were not present in these strains. Even though only B. tequilensis ST816CD displayed γ-hemolysin production, both selected strains were found to produce gelatinase and biogenic amines, which are considered as either potential virulence- or health-related factors. Moreover, the strains were susceptible to a variety of antibiotics except for the penicillin G [1 IU/disc] resistance of B. tequilensis ST816CD. Both strains showed proteolytic activity. Additionally, both strains showed low hydrophobicity based on bacterial adherence measured by hydrocarbons (n-hexadecane).